2019
DOI: 10.1177/2058738419863238
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T-cells and their impacts on cytokine profile of end-stage renal disease patients suffering from systemic lupus erythematosus

Abstract: Autoimmunity is an identified factor for development of end-stage renal disease (ESRD). Regulatory T-cells (Tregs) play a fundamental role in preventing autoimmunity. This study aimed to determine Treg frequency and its effects on cytokine profile of ESRD patients with and without systemic lupus erythematosus (SLE). Moreover, this study also determines how Treg number is affected by blood transfusion and gender. Peripheral blood mononuclear cells were isolated from 26 ESRD and 10 healthy subjects and stained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Moreover, protein-energy malnutrition (PEM), a common and severe complication of CKD, induces T-lymphopenia and T-lymphocyte dysfunction ( 33 ). Several studies indicated that ESKD patients have T-lymphocyte dysfunctions, such as the reduction of regulatory T-cells (Tregs), a subgroup of CD4 + T cells ( 34 , 35 ). Furthermore, because Tregs inhibit systemic inflammation and CVD, deficiency of Tregs might be one reason for some complications in ESRD patients, including CVD ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, protein-energy malnutrition (PEM), a common and severe complication of CKD, induces T-lymphopenia and T-lymphocyte dysfunction ( 33 ). Several studies indicated that ESKD patients have T-lymphocyte dysfunctions, such as the reduction of regulatory T-cells (Tregs), a subgroup of CD4 + T cells ( 34 , 35 ). Furthermore, because Tregs inhibit systemic inflammation and CVD, deficiency of Tregs might be one reason for some complications in ESRD patients, including CVD ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…60 These cells have well-known roles in suppressing different cells from the immune system and inhibiting productions of pro-inflammatory cytokines leading to tumor progression via the increment of the tumor cell escape from the immune system and promotion of tumor growth. [61][62][63][64][65][66]…”
Section: Discussionmentioning
confidence: 99%
“…The influence of ESRD or dialysis therapy on the development of BP remains to be elucidated. Although the reduction of regulatory T cells has been reported to affect the predominance of BP in elderly population [ 19 , 20 ], circulating regulatory T cells were not decreased in ESRD patients, compared with healthy subjects [ 31 ]. In addition, circulating regulatory T cell level was independent of glomerular filtration rate and serum levels of urea nitrogen and creatinine [ 31 ].…”
Section: Discussionmentioning
confidence: 99%